Reliability of assessing interproximal bone loss by digital radiography: intrabony defects - Wolf, Britta; Bethlenfalvy, Eric von; Haßfeld, Stefan; Staehle, Hans Jörg; Eickholz, Peter (Journal of clinical periodontology, 2001)
The aim of the present study was to assess the reproducibility and validity of linear measurements of interproximal bone loss in intrabony defects on digitized radiographic images after application of different filters and magnifications.
Gesehen am 26.02.2021